Pain Management in the Community: The Empowerment of District on Collaboration of Complementary Nursing at Bukittinggi, West Sumatera - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola; Febrina, Cory; Khairunnisa, Cindy Wahyu (Salus Publica: Journal of Community Service, 2023)
Pain is a global health issue. It is estimated that every year 20% of the world's population experiences pain and half of this is chronic pain. In Indonesia there has been no large-scale research discussing the prevalence and quality of all types of pain. Indonesia also does not yet have practical parameters for assessing pain, patient comfort levels, and the effect of pain on the quality of life of the Indonesian people. This Community Service (PKM) seeks to provide training and raise information about pain treatment in one of the districts of Bukittinggi, West Sumatera, through socializing and outreach to the community. The strategy employed in this PKM includes counseling about pain management in the community and how to handle it. This PKM obtained an increase in the knowledge and skill of community members in controlling their pain. According to the findings of monitoring and analyzing PKM activities, the community health service was ready to improve people's pain management strategies. It is believed that this activity will be beneficial in enhancing the knowledge and experience of pain management that may be used in the community health service by individuals and their families, particularly in non-pharmacological approaches as complementary pain management nursing.